The Enduring Influence of Religion on Senators' Legislative Behavior - Arnon, Daniel (Journal for the scientific study of religion, 2018)
Does a senator's personal religion influence their legislative behavior in the Senate? To date, empirical research has answered this question only using senators' religious traditions, while more concurrent work implies that religion should be measured as a multifaceted phenomenon. This study tests this proposition by compiling a unique data set of senators' religion, conceptualized and measured by three different elements-belonging, beliefs, and behavior. The study estimates the association between these three religious facets and senators' legislative behavior on economic, social, and foreign policy issues, while controlling for their constituencies' political and religious preferences. It finds that religious beliefs are a strong predictor of senators' legislative behavior, while religious tradition and behavior are mostly not. Furthermore, it finds that religious beliefs are associated with legislative behavior across a wide array of policy areas and are not confined to sociocultural issues.